Human exposure to halogenated and organophosphate flame retardants through informal e-waste handling activities - A critical review. (1st January 2021) - Ma, Yulong; Stubbings, William A.; Cline-Cole, Reginald; Harrad, Stuart
Abstract: Informal electrical and electronic waste (e-waste) handling activities constitute a potentially important source of halogenated (HFRs) and organophosphate flame retardants (OPFRs) to the environment and humans. In this review, two electronic databases (ScienceDirect and Web of Science Core Collection) were searched for papers that addressed this topic. A total of 82 relevant studies (including 72 studies selected from the two databases and 10 studies located from the references of the first 72 selected studies) were identified that reported on human external and internal exposure to HFRs and OPFRs arising as a result of informal e-waste handling activities. Compared to the general population, higher levels of external exposure (i.e., inhalation, ingestion, and dermal absorption) and internal exposure (i.e., blood serum, hair, breast milk, urine, and other human matrices) to HFRs and OPFRs were identified for e-waste recyclers and residents inhabiting e-waste dismantling and recycling zones, especially for younger adults and children. Food intake and dust ingestion were the dominant exposure pathways for the majority of brominated flame retardants (BFRs) and dechlorane plus (DP); while inhalation was identified as the most significant pathway of human exposure to OPFRs in informal e-waste sites. The majority of research to date has focused on China and thus future studies should be conducted in other regions such as Africa and South Asia. Other suggested foci of future research are: examination of exposure via dermal contact with e-waste, dietary exposure of local populations to OPFRs, confirmation of the existence of and cause(s) of the higher body burdens of females compared with males amongst populations impacted by informal e-waste handling, and characterisation of exposure of such populations to chlorinated paraffins. Graphical abstract: Image 1 Highlights: Food intake is the dominant pathway of human exposure to BFRs and DPs. Inhalation is the dominant pathway of human exposure to OPFRs. Human exposure to HFRs through dermal absorption is likely underestimated. HFR levels are increasing with increasing duration of e-waste handling activity. Females may be more exposed than males in e-waste impacted areas. Abstract : Main findings: Inhalation contributes most to human exposure to OPFRs, and dietary intake contributes most to human exposure to BFRs and DPs. Children and females are more exposed.